Exploring Interfaith Connections at Sobi Hill, Ilorin, Nigeria: A Comprehensive Investigation - Ogunbiyi, Olatunde Oyewole; Fahm, Abdulgafar Olawale; Akande, Lydia Bosede (Universitas Muhammadiyah Magelang, 2023)
This study delves into the interfaith dynamics at Sobi Hill, Ilorin, Nigeria, a communal holy natural place interwoven with Islam and Christianity. Using a qualitative case study approach with interviews, observations, and document analysis, the research explores Sobi Hill as a shared ground for spiritual practices, facilitating interfaith encounters and dialogue. The hill serves as a backdrop for rituals like prayer, pilgrimage, and tourism, promoting mutual understanding among practitioners of different faiths. Positive interfaith experiences are highlighted as contributors to peaceful coexistence and social cohesion. However, the investigation reveals challenges faced by such places, including conflicting beliefs, environmental degradation, and inadequate management. The study advocates for sustainable management practices recognizing the cultural and religious significance of these sites, emphasizing their preservation for future generations. In conclusion, the research provides insights into the interfaith connections at Sobi Hill and addresses broader challenges confronting communal holy natural places. The findings underscore the importance of fostering harmonious coexistence among diverse faith communities and advocate for effective management strategies to safeguard these sacred sites for cultural, religious, and environmental sustainability.